Willingness to Pay and Time Trade-off in Thai Patients with Port-Wine Stains - Jantarakolica T. (2023)
Background: Port-wine stains are congenital vascular abnormalities that impact children’s and parents’ quality of life (QoL). There are currently no established criteria for assessing the quality of life in PWS patients. Utility measures such as willingness-to-pay (WTP) and time trade-off (TTO) can be used to quantify disease burden, impact on QoL, and assess the cost-effectiveness of interventions. Methods: This was a cross-sectional questionnaire-based survey study in Thailand from July 2021 to April 2022. The questionnaire included sociodemographic data and preference-based measurement, WTP and TTO. The primary outcome was a WTP and TTO for PWS laser treatment. The subsample analysis for the primary outcome was based on gender (male and female) and age (<5 years and ≥5 years). The household income was measured for time trade-off outcome. Results: Out of 46 respondents, WTP for the base case at 40% improvement cost 6109.01 baht per visit. Patients were willing to spend their time 9.95 hours per visit for a clinical improvement of 40%. Female was willing to pay and spend more time than male, while those aged≥5 years were willing to pay and spend more time than those aged <5 years. High household income >100k per month willing to spend less time than lower income groups. Conclusion: There were obvious correlations between WTP and TTO with clinical outcomes. Utility indicators such as WTP and TTO can be used to measure disease burden, impact on QoL, and assess the cost-effectiveness of interventions. WTP and TTO could provide a more personalized approach to improving QoL, considering each patient’s unique treatment plan and priority. This could help with patient uncertainty and long-term planning strategies to increase the QoL cost-effectively.